Effectiveness of Kinesiotaping in Reducing Low Back Pain among Elderly Individuals - Widyawati, Fiqi; Pristianto, Arif (P3M Universitas 'Aisyiyah Surakarta, 2025)
Background Low Back Pain (LBP) is a musculoskeletal disorder characterized by discomfort in the lower back region, sometimes accompanied by radiating pain to the lower extremities. LBP is common in individuals aged over 35 years due to degenerative changes such as tissue damage and decreased intervertebral fluid, which reduce spinal and muscular stability. In elderly populations (>60 years), reduced muscle strength exacerbates LBP symptoms, significantly impairing daily function. Kinesiotaping is a physiotherapy technique used to improve musculoskeletal function and support natural healing, including in cases of LBP. Objective This study aimed to determine the effectiveness of kinesiotaping in reducing LBP symptoms among elderly individuals. Methods A quantitative descriptive approach with a one-group pretest–posttest design was employed. The study was conducted at Car Free Day (CFD) Colomadu, Karanganyar Regency, Central Java, in July 2024. A total of 40 elderly participants were recruited. Data were collected using the Keele Start Back Screening Tool questionnaire. Results Among the 40 elderly participants (62.5% female), most experienced LBP classified as minimal disability (50.0%). Post-intervention assessments showed improvements in pain scores, suggesting a positive effect of kinesiotaping on LBP symptoms. Conclusion Kinesiotaping appears to be an effective intervention for reducing low back pain in elderly individuals, particularly in those with minimal functional disability.